δ-Aminolaevulinate dehydratase, the regulatory enzyme of the haem-biosynthetic pathway in Neurospora crassa - Muthukrishnan, S. (1972)
The activity of δ-aminolaevulinate dehydratase is very low in the mould Neurospora crassa compared with the activities detected in bacterial and animal systems. The enzyme is inducible in iron-deficient cultures by addition of iron and is repressed by protoporphyrin. The properties of the purified enzyme indicate its allosteric nature and susceptibility to feedback inhibition by coproporphyrinogen III. Neurospora extracts also contain a protein inhibitor of the enzyme and a small-molecule activator, which appears to be associated with the enzyme. The regulatory function of this enzyme in vivo is correlated with the accumulation of δ-aminolaevulinic acid in normal cultures of N. crassa. The decay curve of the iron-induced enzyme in vivo shows a biphasic pattern, with one of the components showing a half-life of 4–5 min.